Salient Calculation at the Single Offshore Breakwater for a Wave Perpendicular to Coastline using Polynomial Approach - Hutahaean, Syawaluddin (International Journal of Advanced Engineering Research and Science, 2020)
Coastal protection planning using offshore breakwater requires an estimation on the formed salient. There are research results using physical model as well as field observation on the relation between the length of breakwater and the position of breakwater with the formed salient. The relation, however, is qualitative in nature. This research develops a calculation method for a formed salient in single offshore breakwater as a result of a wave that is perpendicular to the breakwater. The model is developed based on the characteristic of stable coastline, i.e. stable coastline that is parallel to the wave crestline forming it, whereas the salient equation is approached with polynomial. The equation provides a good result, i.e. the measurement of salient that is very much in accordance with the result of previous research using physical model or field measurement.